Application of monoclonal and polyclonal antibodies to Hb Bart's for the detection of α thalassemias - Makonkawkeyoon L. (2014)
Using a mouse monoclonal antibody (mAb) ("2D4") with high specific reactivity to Hb Bart's and a rabbit polyclonal antibody ("RPB") with high reactivity to Hb Bart's but low reactivity to HbF, an ELISA assay was developed for the quantification of Hb Bart's in hemolysates of peripheral blood. In the preliminary study, hemoglobin solutions containing 4,000 μg/mL of hemoglobin were analyzed for the concentration of Hb Bart's in samples collected from the following children and adult subjects of HbH families: 12 children with deletional HbH disease (--/-α3.7) or nondeletional HbH disease (HbH disease with HbCS) (--/α csα), 12 adults with α0 thalassemia (--/αα), 12 adults with deletional or nondeletional α+ thalassemia (-α3.7/αα or αα/αcsα) and 12 normal adult subjects (αα/αα). The mean ± S.D. of Hb Bart's concentration in those with deletional HbH disease or HbH disease with HbCS, α0 thalassemia, deletional or nondeletional α+ thalassemia, and normal subjects were 1,374±210 (range 1,164-1,584), 1,118±357 (range 761-1,475), 451 ± 230 (range 221-681), and 0 ng/mL, respectively. When the developed ELISA was further evaluated with additional samples of various types of α thalassemia, including: 18 with deletional HbH disease (--/-α3.7); 21 of nondeletional HbH disease (HbH disease with HbCS) (--/αcsα); 33 with α0 thalassemia (--/αα); 19 with nondeletional α+ thalassemia (αα/αcsα); 11 with deletional α+ thalassemia (-α3.7/ αα) and 58 normal subjects (αα/αα). It was found that the levels of Hb Bart's in deletional α+ thalassemia was significantly lower than in α0 thalassemia (p<0.001). The levels of Hb Bart's in α0 thalassemia was also significantly lower than in nondeletional and deletional HbH diseases (p=0.023 and p<0.001, respectively). When all types of α thalassemia were compared with normal subjects, the Hb Bart's levels in all types of α thalassemia were significantly higher (p<0.0001). All of our results indicated that the developed ELISA was highly sensitive and specific for quantitative determination of Hb Bart's in hemolysates. The ELISA assay might be used as a rapid screening test for the detection of α thalassemias in general population. © Makonkawkeyoon et al.